Crisis, Otherness and Integration. Local policies in South Eastern Europe: The case of Rhodes island - Kimourtzis, Panagiotis; Kokkinos, Georgios; Papageorgiou, Ioannis V; Kypriotis, Dimitris (Advances in Social Sciences Research Journal, 2017)
The density of the refugees and migrants wave in South Eastern Europe, along with the socioeconomic situation within and beyond Europe, shape the context and the agenda of the debate regarding the presence of Others in the European societies. The premises of that debate range from the practical considerations, such as the economic impact of securing the provision of essential necessities to the population in movement, to questions regarding the management of the integration of the current mixed migration flows. The conjuncture in which this debate occurs in the European level, namely the combination of economic crisis along with the emergence of centrifugal and xenophobe tendencies in many countries, render this debate significantly important. In an attempt to overcome the condensation of contradictions of the debate, innovative solutions could focus on researching and analysing the qualitative characteristics of the harmonic symbiosis between culturally diverse social groups at the local level. This article discusses the characteristics of the “embedded diversity” of the Muslim community on Rhodes island and its relations with the dominant Christian population and the new cultural diversity of refugees and immigrants. Based on that, the article analyses the significance of the local social conditions that could facilitate the integration of Others. The article concludes with indicative policy recommendations that base integration attempts on the particularly local social conditions.